I INCREASED RISK OF LYMPHOMA IN MEN INFECTED WITH TUBERCULOSIS - guangliang Chen (Mediterranean Journal of Hematology and Infectious Diseases)
Purpose: To identify factors associated with lymphoma in patients with anterior Mycobacterium tuberculosis (TB).